Absence of gene flow between diploids and hexaploids of Aster amellus at multiple spatial scales - Münzbergová, Z; Surinová, M; Castro, S (Heredity, 2013)
The potential for gene exchange across ploidy levels has long been recognized, but only a few studies have explored the rate of gene flow among different cytotypes. In addition, most of the existing knowledge comes from contact zones between diploids and tetraploids. The purpose of this paper was to investigate relationships between diploid and hexaploid individuals within the Aster amellus aggregate. A. amellus is known to occur in diploid and hexaploid cytotypes in Europe, with a complex contact zone in central Europe. Patterns of genetic diversity were investigated using seven microsatellite loci at three different spatial scales: (1) in the single known mixed-ploidy population; (2) in populations at the contact zone and (3) in a wider range of populations across Europe. The results show clear separation of the cytotypes at all three spatial scales. In addition, analysis of molecular variance strongly supported a model predicting a single origin of the hexaploids, with no or very limited gene flow between the cytotypes. Some hexaploid individuals found in the mixed-ploidy population, however, fell into the diploid cluster. This could suggest recurrent polyploid formation or occasional cross-pollination between cytotypes; however, there are strong post-zygotic breeding barriers between the two cytotypes, making the latter less plausible. Overall, the results suggest that the cytotypes could represent two cryptic species. Nevertheless, their formal separation is difficult as they cannot be distinguished morphologically, occupy very similar habitat conditions and have largely overlapping distribution ranges. These results show that polyploid complexes must be treated with caution as they can hide biological diversity and can have different adaptation potentials, evolving independently.
Keywords: Models, Genetic; fylogeografie; Polyploidy; modely genetické; Genes, Plant; analýza hlavních komponent; diploidie; Phylogeography; Gene Flow; Diploidy; Bayes Theorem; Europe; mikrosatelitní repetice; Aster Plant; Evropa; rostlinné geny; Aster; genetická variace; Microsatellite Repeats; Bayesova věta; Genetic Variation; Principal Component Analysis; tok genů; polyploidie